Effect of a New Synergistic Combination of Low Doses of Acetylsalicylic Acid, Caffeine, Acetaminophen, and Chlorpheniramine in Acute Low Back Pain - Voicu, Victor A.; Mircioiu, Constantin; Plesa, Cristina; Jinga, Mariana; Balaban, Vasile; Sandulovici, Roxana; Costache, Ana Maria; Anuta, Valentina; Mircioiu, Ion (Frontiers in Pharmacology, 2019)
Present paper continues a more complex research related to the increased synergism in terms of both anti-inflammatory and analgesic effect obtained by the addition of chlorpheniramine (CLF) to the common acetylsalicylic acid (ASA), acetaminophen (PAR) and caffeine (CAF) combination. This synergistic effect was previously highlighted both in-vitro in rat models and in-vivo in the treatment of migraine. The aim of the research was to further evaluate the analgesic effect of a synergistic low dose ASA-PAR-CAF-CLF combination in the treatment of low back pain, in a parallel, multiple dose, double blind, active controlled clinical trial. A number of 89 patients with low back pain of at least moderate intensity were randomly assigned to receive Algopirin® (ALG), a combinational product containing 125 mg ASA, 75 mg PAR, 15 mg CAF and 2 mg CLF, or PAR 500 mg, drug recognized by American Pain Society as “safe and effective” in the treatment of low back pain. One tablet of the assigned product was administered three times a day for seven consecutive days. The patients evaluated their pain level using a Visual Analog Scale prior administration, and at 1, 2, 4 and 6 hours after the morning dose. Time-course of effect was similar in structure and size for both treatments. Pain relief appeared rapidly and steadily increased over four hours after drug administration. Differential pain curves of ALG and PAR were very similar and comparable with the previously determined ALG analgesia pattern in migraine. Differences between the daily mean pain scores were not statistically significant for the two treatments. Similar results were obtained for the sum of pain intensity differences (SPID) for 0 -4 h and 0 – 6 h intervals as well as for the time-course of the proportion of patients with at least 30% and at least 50% pain relief. In conclusion, in spite of very small doses of active components, ALG proved equally effective to the standard low back pain treatment and therefore a viable therapeutic alternative, mainly for patients with gastrointestinal and hepatic sensitivity.